Recommendations for the Diagnosis, Prevention, and Control of Coronavirus Disease-19 in Children—The Chinese Perspectives - Fang, Feng; Chen, Yu; Zhao, Dongchi; Liu, Tonglin; Huang, Yongjian; Qiu, Liru; Hao, Yan; Hu, Xiaolin; Yin, Wei; Liu, Zhisheng; Jin, Runming; Ning, Qin; et al. (Frontiers in Pediatrics, 2020)
Ever since SARS-CoV-2 began infecting people by the end of 2019, of whom some developed severe pneumonia (about 5%) which could be fatal (case-fatality approximately 3.5%), the extend and speed of the COVID-19 outbreak has been phenomenal. Within 2 and half months (by March 18, 2020) over 191,127 COVID-19 patients have been identified in 161 countries. By then, over 700 paediatric patients were confirmed to have COVID-19 in China, with only about 58 diagnosed elsewhere. By now, there are thousands of children and adolescents infected. Chinese paediatricians would like to share their experience of how these patients were managed in China and the key recommendations which had guided them meeting the evolving challenges. A group of experts were summoned by the Chinese Paediatric Society and Editorial Board of Chinese Journal of Paediatrics to extract informative data from a survey on confirmed COVID-19 paediatric patients in China. Consensus on diagnosis, management and prevention of paediatric COVID-19 were drawn up based on the analysis of such data plus insights gained from the past SARS & MERS coronavirus outbreaks. Relevant cumulating experiences from physicians managing adult patients, expeditated reports on clinical and scientific COVID-19 and SARS-CoV-2 data, and the National Health Committee guidelines on COVID-19 management were integrated into this proposal.